Head-to-head comparison of family history of colorectal cancer and a genetic risk score for colorectal cancer risk stratification - Weigl, Korbinian; Knebel, Phillip; Hoffmeister, Michael; Brenner, Hermann (Clinical and translational gastroenterology, 2019)
OBJECTIVES: Family history (FH) is associated with increased risk of colorectal cancer (CRC). We aimed to examine the potential for CRC risk stratification by known common genetic variants beyond FH in a large population-based case-control study from Germany. METHODS: Four thousand four hundred forty-seven cases and 3,480 controls recruited in 2003-2016 were included for whom comprehensive interview, medical, and genomic data were available. Associations with CRC risk were estimated from multiple logistic regression models for FH and a genetic risk score (GRS) based on 90 previously identified risk variants. RESULTS: CRC in a first-degree relative was associated with a 1.71-fold (95% confidence interval 1.47-2.00) increase in CRC risk. A higher risk increase (odds ratio 2.06, 95% confidence interval 1.78-2.39) was estimated for the GRS when it was dichotomized at a cutoff yielding the same positivity rate as FH among controls. Furthermore, the GRS provides substantial additional risk stratification in both people with and especially without FH. Equal or even slightly higher risks were observed for participants without FH with a GRS in the upper 20% compared with participants with FH with a GRS below median. The observed patterns were confirmed in a replication study. DISCUSSION: In contrast to common perception, known genetic variants do not primarily reflect some minor share of the familial excess risk of CRC, but rather reflect a substantial share of risk independent of FH.